Peningkatan Kemampuan Membaca Permulaan Siswa Menggunakan Metode SAS dengan Media Kartu Huruf pada Siswa Kelas 1 MIS Muhammadiyah Sibatua - Nurmila Auliya; Sumarni Sumarni; Tarman A. Arif; Herlina Herlina (Departement of Mathematics Education, 2023)
This research is a Classroom Action Research, as part of the Teacher Professional Consolidation Practice (P2K) activities by students of the University of Muhammadiyah Makassar. This Classroom Action Research was carried out as a way to improve the initial reading ability of the first graders of MIS Muhammadiyah Sibatua. It is known that reading is the most important thing to be taught to children. It can be seen that most students, especially in class I, still do not know letters and are able to read fluently. For this reason, the purpose of this classroom action research is to improve students' initial reading skills using the SAS method with letter card media. This research consists of two cycles, namely Cycle I and II. The steps taken are planning, discussion, observation and reflection. The results of this study are the average value of students' initial reading skills from cycle I to cycle II has progressed by 4.67. The level of student learning mastery from cycle I to cycle II has increased by 16.62%. And the results of the overall observation of students in the first cycle is 76.41% while in the second cycle is 93.03%. It can be concluded that students' early reading learning using the SAS method with letter card media can improve the initial reading skills of Class I MIS Muhammadiyah Sibatua students.